1992
DOI: 10.1051/jp3:1992141
|View full text |Cite
|
Sign up to set email alerts
|

Propriétés thermodynamiques et de transport des plasmas issus de la vaporisation des isolants PTFE et PE

Abstract: At atmospheric pressure, the values of density, enthalpy, specific heat, sonic velocity, viscosity, thermal and electrical conductivities have been calculated for plasmas of PE and PTFE in the temperature interval 5 000 K-30 000 K. In hypothesis of LTE, equilibrium composition is calculated using the classical equations of thermodynamic, and transport coefficients are calculated using the Chapman-Enskog method. The accuracy of results is discussed in connection with the selection of the collision integrals of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…The chemical equilibrium for the five plasmas formed in insulator vapours are shown in figures 1 to 5 in the temperature range 1000 K to 10 000 K. The results are in good agreement with other authors [2,[5][6][7] in the temperature range 5000-10 000 K, although these authors do not take the same chemical species into account, especially the polyatomic species.…”
Section: Composition Of Plasmas Produced In Insulator Vapourssupporting
confidence: 87%
See 1 more Smart Citation
“…The chemical equilibrium for the five plasmas formed in insulator vapours are shown in figures 1 to 5 in the temperature range 1000 K to 10 000 K. The results are in good agreement with other authors [2,[5][6][7] in the temperature range 5000-10 000 K, although these authors do not take the same chemical species into account, especially the polyatomic species.…”
Section: Composition Of Plasmas Produced In Insulator Vapourssupporting
confidence: 87%
“…For a better understanding of the interaction between the insulator wall and the arc, we need to know the composition and thermodynamic properties of the plasma formed in insulator vapours at low temperature. Many calculations resolving mass action laws [2,[5][6][7] and others using the Gibbs free energy minimization method [3,4] have already been made in the temperature range 5000-30 000 K. To complete these studies, we determine the composition below 5000 K. Previous experiments near the insulator wall during the interaction have shown that the temperature is low (< 8000 K) [8].…”
Section: Introductionmentioning
confidence: 99%
“…When the solid phase of carbon has not yet been formed the results are identical in the two cases. The concentrations between temperatures of 5000 and 10 000 K were given in our previous paper [15] and for temperatures higher than 10 000 K they have been given in various papers: PMMA in [1,6], PA6-6 in [1,5,6,11], PETP in [1,6], POM in [1,6] and PE in [1,4].…”
Section: Resultsmentioning
confidence: 99%
“…Circuit breakers were the subject of several theoretical and experimental studies (André, et al, 2004;André, 1996;André, 1997, PP. 475-493;Abbaoui, et al, 1992;Andanson, et al, 1979;, PP. 1339-1359.…”
Section: Introductionmentioning
confidence: 99%